If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(5 + n) = 3 + -4(12 + -6n) (5 * 9 + n * 9) = 3 + -4(12 + -6n) (45 + 9n) = 3 + -4(12 + -6n) 45 + 9n = 3 + (12 * -4 + -6n * -4) 45 + 9n = 3 + (-48 + 24n) Combine like terms: 3 + -48 = -45 45 + 9n = -45 + 24n Solving 45 + 9n = -45 + 24n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-24n' to each side of the equation. 45 + 9n + -24n = -45 + 24n + -24n Combine like terms: 9n + -24n = -15n 45 + -15n = -45 + 24n + -24n Combine like terms: 24n + -24n = 0 45 + -15n = -45 + 0 45 + -15n = -45 Add '-45' to each side of the equation. 45 + -45 + -15n = -45 + -45 Combine like terms: 45 + -45 = 0 0 + -15n = -45 + -45 -15n = -45 + -45 Combine like terms: -45 + -45 = -90 -15n = -90 Divide each side by '-15'. n = 6 Simplifying n = 6
| 7x+5=7(x-2) | | 5-4h=2h-13 | | 11x-27=6x-7-5x | | 5+2x=66 | | 1.2+0.1x=0.4x-4.2 | | 10n+8s=50 | | 3=-20x+2 | | c-0.55c=54 | | 6u+8=8u | | X-1=y*4000 | | 6=2(v+5)-6v | | p+0.04p=114.4 | | .04x=.26 | | 63-2v=7v | | g(z)=-5z-5 | | .04x=26 | | Y=2x^2+12x+20 | | 6y+3x=93 | | 42=8x-(4x-8)+7(x-3) | | -24-3x=-3+4(1-2x) | | 0.25p-4.5=3 | | d=30(15) | | 55y+8x=90 | | 5(2x+3)+3=3(2x+6)-10 | | 60x+11y=1 | | x/27=26 | | X+2=y*5000 | | d=25(20) | | 27/x=26 | | -10-9h-10=-6h+100 | | 0.25p-4.6=3 | | 18+22=-5(7x-8) |